NAIRU Uncertainty and Nonlinear Policy Rules - Meyer, Laurence H; Swanson, Eric T; Wieland, Volker W (American Economic Review, 2001)
Meyer (1999) has suggested that episodes of heightened uncertainty about the NAIRU may warrant a nonlinear policy response to changes in the unemployment rate. This paper offers a theoretical justification for such a nonlinear policy rule, and provides some empirical evidence on the relative performance of linear and nonlinear rules when there is heightened uncertainty about the NAIRU.